Dynamic Material Properties of Kalgoorlie Basalt Rock - Zhang, Xihong; Chiu, Yuwen; Hao, Hong; Hsieh, Ariel; Dight, Phil; Liu, Kewei (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In this study, the basalt rock extracted from the Kalgoorlie region of Western Australia is intensively studied on its compressive properties under both static and dynamic loads covering strain rate between 2.22 × 10-6/s to 408/s. The ultimate compressive strength and corresponding failure strain are quantified. The test results show that Kalgoorlie basalt rock exhibits high sensitivity to strain rate effect on its compressive strength especially above 100/s and dynamic increment factor up to 2.3 at strain rate 403/s. The failure strain also shows dependency to high strain rate. Discussion is made on fragment analysis which found the natural heterogeneous and anisotropic of WA basalt rocks cause variations on its compressive strength and dependent on the failure angle of the joints (layer formation). The dynamic increase mechanism on material compressive properties is observed to be correlated to the failure crack path formation, which can be explained through the fracture process captured from high-speed camera images analysis. Comparisons are also made on rock strengths with others’ test data. A novel method based on numerical modelling is introduced which removes the influence of lateral inertia effect and specimen end friction effect out of the laboratory testing results. The true dynamic increase factor (DIF) for Kalgoorlie basalt rock at different strain rates are derived for more accurate analysis and design.